ANALYSIS AND EVALUATION OF THE DRAINAGE NETWORK SYSTEM IN THE HOUSING AREA OF VILA RIZKI ILHAMI 2 SAWANGAN, DEPOK-WEST JAVA - Ashari, Ridwan Jamaludin; Heryansyah, Arien (ASTONJADRO, 2021)
The impact that occurs from the rampant development of residential areas will certainly make the volume of surface water flow or run off become large. Drainage is a system created to deal with the problem of excess water flow that is above the surface of the earth, some of the things that cause excess water are caused by high water intensity and the long duration of rain. In this study, the problem that occurred was in the drainage network in the residential area of Vila Rizki Ilhami 2 Sawangan, which was a transfer of land functions from infiltration land into a residential area. Evaluation that must be done is covering hydrological analysis and hydraulics analysis to get the amount of flood discharge plan that will be used to analyze the capacity of the planned channel so that no flooding occurs at the location of the settlement area when the settlement is built, recommendations for drainage system design and determine the size of the river dimension / size / times that should be made when accommodating water discharge during maximum rain so that the flood control system can be well integrated. With 3 methods of calculating rainfall, the method of calculation is selected using the gumbel method which is SNI (Indonesian National Standard) with a return period of 2 years, 5 years and 10 years. From the evaluation obtained is to add height height or free board to accommodate flood discharge plan.